2015
DOI: 10.1121/1.4931906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intervening tissues on ultrasonic backscatter measurements of bone: An in vitro study

Abstract: Ultrasonic backscatter techniques are being developed to diagnose osteoporosis. Tissues that lie between the transducer and the ultrasonically interrogated region of bone may produce errors in backscatter measurements. The goal of this study is to investigate the effects of intervening tissues on ultrasonic backscatter measurements of bone. Measurements were performed on 24 cube shaped specimens of human cancellous bone using a 5 MHz transducer. Measurements were repeated after adding a 1 mm thick plate of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…FSAB is another backscatter parameter that has been identified as potentially useful for ultrasonic bone assessment. 26,[29][30][31]33,35 Measured values of FSAB from the OCRF specimens are similar, but slightly greater (less negative) than values reported for cancellous bone. nMBD is a relatively new backscatter parameter that may be less sensitive to the effects of gate duration and position because it is corrected (normalized) for these effects.…”
Section: Pcfsupporting
confidence: 48%
See 2 more Smart Citations
“…FSAB is another backscatter parameter that has been identified as potentially useful for ultrasonic bone assessment. 26,[29][30][31]33,35 Measured values of FSAB from the OCRF specimens are similar, but slightly greater (less negative) than values reported for cancellous bone. nMBD is a relatively new backscatter parameter that may be less sensitive to the effects of gate duration and position because it is corrected (normalized) for these effects.…”
Section: Pcfsupporting
confidence: 48%
“…Two types of ultrasonic transducers were used. A 0.5 MHz diameter planar transducer (Panametrics V301, Waltham, MA) with a 25.4 mm element diameter, 53.8 mm near field length, and 6 mm beam diameter was used to perform SOS and attenuation Cellular aluminum foam Velocity, attenuation, B/A a Ji et al 11 Le et al 12 Zhang et al 13 Lee [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The beam diameters of both transducers were determined from technical notes provided by the manufacturer. 40 Measurement configurations are illustrated in Fig.…”
Section: B Ultrasonic Scanning Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, intervening tissues that lie between the transducer and ultrasonically interrogated region may produce errors in AIB measurements of bone. 31 In addition, recent studies have shown that AIB may depend strongly on the portion of the backscatter signal that is analyzed. 32,33 AIB is determined by measuring the power in a portion of the backscatter signal defined by a "gate" that is used to select that portion for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters based on this technique have been shown to correlate strongly with bone density, and to be relatively insensitive to errors caused by intervening tissues that lie between the transducer and ultrasonically interrogated region of bone. 31,35 In addition, theoretical considerations have led to a concept called "normalization" that may reduce the dependence of backscatter difference parameters on the size and location of analysis gates applied to the backscatter signal. 35 These features address the major limitations of AIB as a bone assessment parameter, while preserving conveniences associated with AIB such as ease of measurement, especially in vivo.…”
Section: Introductionmentioning
confidence: 99%